Structural color three-dimensional printing by shrinking photonic crystals - Yejing Liu (Nature Portfolio, 2019)
The ability to print arbitrary colors and shapes in all three dimensions at microscopic length scales is still lacking. Here, the authors introduce a means to produce three-dimensionally-printed photonic crystals with a periodicity as small as 280 nm, achieving sub-100-nm features with a full range of colors.